Mutant PfCRT Can Mediate Piperaquine Resistance in African Plasmodium falciparum With Reduced Fitness and Increased Susceptibility to Other Antimalarials. (9th September 2022) - Wicht, Kathryn J; Small-Saunders, Jennifer L; Hagenah, Laura M; Mok, Sachel; Fidock, David A
Abstract: Background: Additional therapeutic strategies could benefit efforts to reverse the recent increase in malaria cases in sub-Saharan Africa, which mostly affects young children. A primary candidate is dihydroartemisinin + piperaquine (DHA + PPQ), which is effective for uncomplicated malaria treatment, seasonal malaria chemoprevention, and intermittent preventive treatment. In Southeast Asia, Plasmodium falciparum parasites acquired PPQ resistance, mediated primarily by mutations in the P falciparum chloroquine resistance transporter PfCRT. The recent emergence in Africa of DHA-resistant parasites creates an imperative to assess whether PPQ resistance could emerge in African parasites with distinct PfCRT isoforms. Methods: We edited 2 PfCRT mutations known to mediate high-grade PPQ resistance in Southeast Asia into GB4 parasites from Gabon. Gene-edited clones were profiled in antimalarial concentration-response and fitness assays. Results: The PfCRT F145I mutation mediated moderate PPQ resistance in GB4 parasites but with a substantial fitness cost. No resistance was observed with the PfCRT G353V mutant. Both edited clones became significantly more susceptible to amodiaquine, chloroquine, and quinine. Conclusions: A single PfCRT mutation can mediate PPQ resistance in GB4 parasites, but with a growth defect that may preclude its spread without further genetic adaptations. Our findings support regional use of drug combinations that exert opposing selective pressures on PfCRT. Abstract : We report that Plasmodium falciparum resistance to piperaquine, an artemisinin-based combination therapy drug, can be achieved in an African strain via a single PfCRT point mutation. Resistance is modest compared to Asian strains and comes with a substantial fitness cost.